A glucomannogalactan from Pleurotus geesteranus: Structural characterization, chain conformation and immunological effect. (1st July 2022) - Liang, Zhenhua; Yin, Zhenhua; Liu, Xiaopeng; Ma, Changyang; Wang, Jinmei; Zhang, Yan; Kang, Wenyi
Abstract: A water-soluble glucomannogalactan was isolated from P . geesteranus fruit bodies by hot water extraction and column chromatography method. The structure, chain conformation and immune effect of PGP-1c (20.9 kDa) were investigated comprehensively based on high purity and neutral sugar content (94.7 ± 0.5%). Confirmed by monosaccharide composition, methylation and NMR analysis, PGP-1c was composed of unsubstituted (1, 6- α -Gal and 1, 6- α -3- O Me-Gal) and monosubstituted (1, 2, 6- α -Gal and 1, 2, 6- α -3- O Me-Gal) galactose units in the backbone through α -(1 → 6) glycosidic bonds and the possible branches that a long-branched chain composed of →3)-Glc-(1 → Man and a few fucoses were connected at the O -2 of galactose with a branching degree of 48%. Through the conformational behavior of the molecular chain, it was observed that PGP-1c might have a long-branched or stacked macromolecular network caused by O -CH3 groups. Moreover, PGP-1c could promote the secretion of NO and cytokines significantly in a dose-dependent manner, which indicated a good immune-enhancing effect. Graphical abstract: Unlabelled Image